(3GdJYhjV aj MhGOK GdSjGQGJ aj VhA Gdabg hGdbVGAs - (3TQja CMeO(B, (3GdWHGNs ((3GdbGgQI(B:s (3GdeQcR Gdbhej ddEUOGQGJ GdbGfhfjI(B,s, 2002)
(3JYQja OYhi GdJYhjV hWHjYJgG hfWGbgG hELQGAGJgG(B-(3WQb GdGKHGJ aj OYhi JYhjV MhGOK GdSjGQGJ(B-(3GQcGf OYhi GdJYhjV aj MhGOK GdSjGQGJ(B-(3GdJYhjV GdeGOj hGdehQhK hGdeDbJ aj MhGOK GdSjGQGJ(B-(3GdUdM aj OYhi JYhjV GdSjGQGJ(B-(3GdMce aj OYhi JYhjV MhGOK GdSjGQGJ hWQb GdWYf YdjgGs
(3GdedGMb U(B.284s
Keywords: (3GdSjGQGJs; (3Gdabg GdGSdGejs; (3MhGOK GdeQhQs; (3bhGfjf hJTQjYGJs